Tumor-infiltrating CD45RO(+) Memory T Lymphocytes Predict Favorable Clinical Outcome in Solid Tumors - Hu, Guoming (Sci Rep, 2017)
The prognostic role of tumor-infiltrating CD45RO(+) memory T lymphocytes (CD45RO(+) T cells) in human solid tumors remains controversial. Herein, we conducted a meta-analysis including 25 published studies with 4720 patients identified from PubMed and EBSCO to assess the prognostic impact of tumor-infiltrating CD45RO(+) T cells in human solid tumors. We found that CD45RO(+) T cell infiltration was significantly associated with improved overall survival (OS) and disease-free survival (DFS) in all types of solid tumors. In stratified analyses, CD45RO(+) T cell infiltration significantly improved 1-year, 3-year and 5-year OS in colorectal, gastric and esophageal cancer, but only 5-year OS in hepatocellular carcinoma. And these cells were positively associated with 1-year, 3-year and 5-year DFS in hepatocellular, colorectal and esophageal cancer. In addition, high density of intratumoral CD45RO(+) T cells inversely correlated with TNM stage of solid tumor. In conclusion, CD45RO(+) memory T lymphocyte infiltration leads to a favorable clinical outcome in solid tumors, implicating that it is a valuable biomarker for prognostic prediction for human solid malignances.